Addition of spironolactone in patients with resistant arterial hypertension (ASPIRANT)--study protocol - Vaclavik, Jan; Sedlak, Richard; Plachy, Martin; Navratil, Karel; Plasek, Jiri; Husar, Roman; Kocianova, Eva; Taborsky, Milos (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
BACKGROUND: There is currently limited data on which drug should be used to improve blood pressure control in patients with resistant hypertension. Recent observational trials reported spironolactone as having good effects. This study is designed to assess the effect of the addition of 25 mg of spironolactone on blood pressure (BP) in patients with resistant arterial hypertension. METHODS: Patients with office systolic BP > 140 mmHg or diastolic BP > 90 mmHg despite treatment with at least 3 antihypertensive drugs including a diuretic, are enrolled in this double-blind, placebo-controlled, multicentre trial. Patients are randomly assigned to receive spironolactone or a placebo at a ratio of 1:1 by the method of simple randomisation. Our primary endpoints are to show a statistically significant difference in the fall of mean day-time systolic and diastolic BP by ambulatory blood pressure monitoring (ABPM), between the spironolactone and placebo groups, after 8 weeks of treatment. Secondary outcomes are changes of serum potassium, natrium, creatinine, body weight, casual blood pressure in office, difference in the fall of mean night-time and 24-hour ABPM BP and treatment response depending on different baseline levels of aldosterone and aldosterone/PRA ratio. DISCUSSION: If spironolactone proves effective, it might become the standard of treatment in patients with resistant arterial hypertension.
Keywords: krevní tlak; Mineralocorticoid Receptor Antagonists; lidé; hypertenze; dvojitá slepá metoda; Antihypertensive Agents; Hypertension; antihypertenziva; Double-Blind Method; Blood Pressure; Spironolactone; spironolakton; antagonisté mineralokortikoidních receptorů; Humans